PENERAPAN MODEL TAKE AND GIVE DENGAN MEDIA GRAFIS DALAM PENINGKATAN PEMBELAJARAN IPS TENTANG PERSIAPAN KEMERDEKAAN INDONESIA PADA SISWA KELAS V SDN 1 TAMBAKAGUNG TAHUN AJARAN 2015/2016 - Anjani, Dwi (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Take and Give Model using Graphic Media in Improving Social Science Learning for The Fifth Grade Students. The objectives of this research is improve to learning outcomes of social science learning through the application of Take and Give model using graphic media. This research is collaborative Classroom Action Research (CAR) conducted in three cycles, consisting of planning, action, observation, and reflection on each cycle. Subjects of this research were 30 students. Techniques of collecting data were test, observation, and interview. Validity of data in this research was analyzed using triangulation of sources and triangulation of technique. Data were analyzed using quantitative and qualitative descriptive analysis. The conclusion of this research is the application of Take and Give model using graphic media can improve social science learning for the fifth grade students of SDN 1 Tambakagung in the academic year of 2015/2016.Keywords: Take and Give model, graphic media, social science learning Abstrak: Penerapan Model Take and Give dengan Media Grafis dalam Peningkatan Pembelajaran IPS pada Siswa Kelas V Sekolah Dasar. Tujuan penelitian ini adalah untuk meningkatkan pembelajaran IPS melalui penerapan model take and give dengan media grafis. Penelitian tindakan kelas kolaboratif ini dilaksanakan dalam tiga siklus yang terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi. Subyek penelitian ini berjumlah 30 siswa. Teknik pengumpulan data berupa tes, observasi, dan wawancara. Validitas data menggunakan triangulasi sumber dan teknik. Analisis data yang digunakan, yaitu analisis data kuantitatif dan kualitatif. Simpulan penelitian ini adalah penerapan model take and give dengan media grafis dapat meningkatkan pembelajaran IPS pada siswa kelas V SDN 1 Tambakagung tahun ajaran 2015/2016.Kata kunci: model take and give, media grafis, IPS